Radioatividade nas premissas de uma UEPS : contribuições de um curso de formação de professores - Aguiar Neto Filho, Manoel (2025)
Education has undergone several transformations, with the goal of students acquiring skills and competencies in different areas of knowledge. Radioactivity Teaching is presented as a link between different curricular components that can and should work harmoniously to promote the development of such skills and competencies. Furthermore, to achieve integrated knowledge, teaching this topic seeks contexts and discussions that can generate reflection and broaden students' worldview, in order to form a critical and conscious citizen. However, some research deals with the Teaching of Radioactivity in Basic Education and the difficulties that teachers from different curricular components encounter when addressing this content in their classes; such difficulties occur due to the different formation the teachers who address these contents go through – generally, chemistry, physics and biology –, or even result from gaps left in teachers' training during undergraduate studies. In this case, the construction of a material with a logical and structured sequence of activities and a continuous teacher training course are elements that can help eliminate or minimize gaps in their training and contribute to the quality of Radioactivity Teaching. Thus, based on these reflections, the question that guided the development of this research arises: In what way can a course organized according to the principles of a potentially significant teaching unit, featuring historical episodes of radioactive accidents, enhance the training of Chemistry teachers in the context of High School? With regard to general objective 1, this thesis intends to promote the Scientific/Chemical Education of high school students, based on the use of historical episodes of radioactive accidents in a PMTU, through an approach containing interdisciplinary elements; and, in turn, with regard to general objective 2, the research aims to promote the initial/continued training of Chemistry teachers, who work in High School, for the use of historical episodes of radioactive accidents in a Potentially Significant Teaching Unit (UEPS), containing interdisciplinary elements. A feasibility study was carried out in order to verify the effectiveness of the educational product developed. The research was characterized by a qualitative approach, with third-year high school teachers from different areas of knowledge as the investigated subjects. The data obtained in the feasibility study were used to improve the educational product and also to build a continued teacher training course. The course is structured in five modules and aims to discuss the theoretical foundations used to develop the educational product. Furthermore, it aims at guiding teachers in applying this product in the classroom in order to verify its viability in different contexts. To this end, the instruments used for data production were interviews, questionnaires and the logbooks of research teachers. Data analysis was performed using Discursive Text Analysis with the help of IRAMUTEQ software. The results obtained with the application of the presented Educational Product were positive and showed signs of significant learning and interdisciplinarity. Teachers and students showed good adherence to the work, which proved to be significant and practical. It is important to emphasize that continued education courses and the production of materials are necessary to assist teachers in the difficult task of promoting Meaningful Learning and interdisciplinarity, since they have a time limit due to the heavy workload and demands they face daily. The Educational Product is freely and publicly available on the website of the Graduate Program in Science and Mathematics Education at the University of Passo Fundo and on the Educapes platform at the link http://educapes.capes.gov.br/handle/capes/1000153.